Pengaruh Lama Fermentasi Terhadap Karakteristik Minuman Probiotik Sari Buah Terong Belanda (Solanum betaceum Cav ) Dengan Lactobacillus sp F213 - Pracheta Febricia, Gede; Ayu Nocianitri, Komang; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPA, 2020)
This research aims to identify the effect of fermentation time on the characteristics of tamarillo juice (Solanum betaceum Cav.) probiotic drinks with the addition of Lactobacillus sp F213 as well as to determine the best time of fermentation that produces the best characteristics of product. Descriptive experimental method design was used in the objective test (total LAB test, total sugar, total acid, pH) and randomized block design in subjective testing (sensory testing). This study uses a treatment that is fermentation time: (18 hours, 20 hours, 22 hours, 24 hours, and 26 hours). The treatment was repeated 3 times to produce 15 experimental units. The data results was described in tables and figures. The results showed treatment with 22 hours fermentation time produced with the best characteristics of the product, namely the total LAB value of 9.44 Log CFU / ml, total sugar 14,16%, total acid 1.50%, pH 4.32 with the preferred orange hedonic test, aroma which is rather liked, the taste scoring test with acidic criteria, and rather sweet and overall acceptance which is rather preferred Keywords: fermentation time, Lactobacillus sp F213, Probiotic drink, Tamarillo juice.